Promoting Medical Tourism In Odisha: A Study on Issues And Challenges In Twin Cities of Cuttack And Bhubaneswar - Sahoo, Shwetasaibal Samanta; Mukunda B G (International Journal of Psychosocial Rehabilitation, 2020)
Although the medical tourism is a recent phenomenon, this sector grows exponentially and emerges as a major force for the growth of services exports worldwide. The term medical tourism has been coined by travel agencies and the mass media to describe the rapidly growing practice of travelling across international borders to obtain hi-tech medical care. It is the fastest growing sector in the 21st century and also because many countries are interested in taking advantage for its economic potential, countries are capitalizing their popularity as tourist destinations by combining high quality medical services at competitive prices with tourist packages. Medical tourism in India is a bird eye view subject in both central and state list. Soaring medical costs, high insurance premiums, increasing number of uninsured and under insured people in developed nations, long waiting period in the home country, availability of high quality health care services at affordable rate, and internet/communication channels in developing countries, cheaper air fares, and tourism aspects are the driving forces of the outbound medical tourism. Odisha, formerly known as Orissa, is a major state in eastern India. When so many other states of India have already made their presence of medical tourism in global competition, Odisha is still lagging behind. The present health care facilities in Odisha are conducive for successful development of medical tourism in the state. However, it requires further improvement and attention by the service providers and policy makers. The study, thus undertaken to explore key issues and challenges in development of medical tourism in twin cities of Cuttack and Bhubaneswar of Odisha & suggest corrective measures to facilitate medical tourism for projecting Odisha as a medical tourism destination.